A Bibliometric Analysis of Research Trends in Spousal Support for Breast Cancer Patients - Liu Y; Zhai Y; Gao L; Zhang G (Journal of Multidisciplinary Healthcare)
Yanping Liu,1 Yanxue Zhai,1,* Limei Gao,1,* Gantang Zhang2 1Nursing Department, Shenzhen Longhua District Central Hospital, Shenzhen, People’s Republic of China; 2Oncology Department, Shenzhen Longhua District Central Hospital, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanxue Zhai; Limei Gao, Email 1032784239@qq.com; 769511958@qq.comBackground: The annual rise in breast cancer incidence is a significant issue that threatens women’s health and imposes various physical and psychological effects on male spouses, while these spouses often serve as the primary source of social support for patients.Purpose: To conduct a systematic analysis of publications, countries, institutions, journals, disciplines, authors, keywords, and references related to spousal support for breast cancer patients using bibliometric methods.Methods: We searched the Web of Science Core Collection (WOSCC) for publications related to spousal support for breast cancer patients from January 2004 to December 2024. CiteSpace (6.4 R1, 64-bit Advanced Edition) and Microsoft Office Excel 2019 were used for bibliometric analysis and chart generation.Results: Our study analyzed 672 articles in the WOSCC database on spousal support for breast cancer patients over the past two decades. These publications have exhibited a trend of fluctuating growth. Research area primarily focuses on oncology, psychology, and nursing, with findings mainly published in Psycho-Oncology and Supportive Care in Cancer. The United States, Canada, and Australia lead this research domain, with the University of California system, Duke University, and Harvard University being the principal research institutions. Laura S. Porter and Donald H. Baucom are among the most prolific authors. The main keyword clusters include #1 caregiving burden, #2 quality of life, #3 sexual health, #4 qualitative study, #5 dyadic coping, and #6 marital status. The references focus on social psychology, intimate relationships, emotional communication, and coping interventions.Conclusion: This bibliometric study analyzes research on spousal support for breast cancer patients during the last two decades, outlining the publications, countries, institutions, journals, disciplines, and authors that have significantly influenced the field. Emerging trends in research on spousal support for breast cancer patients emphasize valuing the caregiving burden endured by spouses, exploring their support experiences, identifying spousal support barriers, and addressing intimacy challenges. Keywords: breast cancer, spouse support, visual analysis, cite space, review, research hotspots